Change Blindness and Misrepresentation - Kirkeby-Hinrup, Asger (2016)
Some proponents of the higher-order thought (HOT) theory of consciousness defend the view that higher-order misrepresentation is possible. In support of this view they have proposed various pieces of empirical evidence. This paper examines one such piece of proposed empirical evidence; Change blindness (CB). CB occurs when a subject fails to detect salient changes in visual scenes. I propose an alternative interpretation of the CB phenomenon on which misrepresentation does not occur. Finally, I examine three lines of reply that might be pursued to defend the claim that CB is evidence of misrepresentation against my interpretation. I conclude that none of the lines of reply succeed in preserving CB as evidence of misrepresentation. The upshot is that, pending further evidence, CB cannot be deployed as empirical evidence in the debate on misrepresentation.